The Study and Analysis of city structure and its permanent development (Case study: Ardabil city) - Moharram Yousefi; Alireza Estelaji; Naser Fallah Tabar (تحقیقات کاربردی علوم جغرافیایی)
The Earth and how it is used have always been the main things in city planning. The analysis and the special and local arrangement of urban use and urban functions are among the important and effective branches of permanent urban development. This paper attempts to analyze quantitatively and qualitatively the city structure of Ardabil with regard to its permanent development. Since it is descriptive and analytic in approach, the three features of capacity, suitability, and social justice in permanent development have been applied. In the first phase, the quantitative analysis of the existing urban use and the capacity analysis were done. The second phase dealt with the qualitative analysis of its suitability using suitability matrix and the analysis of social justice with the closest neighbor model and SWOT model. The quantitative and qualitative results show that most urban uses are deficient. Also, the highest unsuitability was in working use and then in official, residential, and educational use. This shows the imbalanced and discordant situation between urban uses that arise from carelessness of city planners.